Analysis of predictors of opioid-free analgesia for management of acute post-surgical pain in the United States. (1st February 2019) - Urman, Richard D.; Böing, Elaine A.; Khangulov, Victor; Fain, Randi; Nathanson, Brian H.; Wan, George J.; Lovelace, Belinda; Pham, An T.; Cirillo, Jessica
Abstract: Objectives: Utilization of opioid-free analgesia (OFA) for post-surgical pain is a growing trend to counter the risks of opioid abuse and opioid-related adverse drug events (ORADEs). However, utilization patterns of OFA have not been examined. In this study, we investigated the utilization patterns and predictors of OFA in a surgical population in the United States. Methods: Analysis of the Cerner Health Facts database (January 2011 to December 2015) was conducted to describe hospital and patient characteristics associated with OFA. Baseline characteristics, such as age, gender, race, discharge status, year of admission and chronic comorbidities at index admission were collected. Hospital characteristics and payer type at index admission were collected as reported in the electronic health record database. Descriptive statistics and logistic regression were used to identify statistically significant predictors of OFA on patient and institutional levels. Results: The study identified 10, 219 patients, from 187 hospitals, who received post-surgical OFA and 255, 196 patients who received post-surgical opioids. OFA rates varied considerably by hospital. Patients more likely to receive OFA were older (OR = 1.06, 95% CI [1.03, 1.10]; p  < .001), or had neurological disorders (OR = 1.24, 95% CI [1.10, 1.39]; p  < .001), diabetes (OR = 1.20, 95% CI [1.08, 1.33]; p  = .001) or psychosis (OR = 1.18, 95% CI [1.01, 1.37]; p  = .030). Patients with obesity and depression were less likely to receive OFA (OR = 0.80, 95% CI [0.67, 0.95]; p  = .010 OR = 0.85, 95% CI [0.73, 0.98]; p  = .030, respectively). Conclusions: Use of post-surgical OFA was limited overall and was not favored in some patient groups prone to ORADEs, indicating missed opportunities to reduce opioid use and ORADE incidence. A substantial proportion of OFA patients was contributed by a few hospitals with especially high rates of OFA, suggesting that hospital policies, institutional structure and cross-functional departmental commitment to reducing opioid use may play a large role in the implementation of OFA.